Scripture's doctrine and theology's Bible : how the New Testament shapes Christian dogmatics - Bockmuehl, Markus N. A.; Torrance, Alan J. (Michigan: Grand Rapids : Baker Academic, 2008)
Scripture's Doctrine and Theology's Bible stems from an illuminating symposium held at the University of St. Andrews that assembled a group of world-class biblical and systematic theologians to answer this fundamental question: To what extent, and on what grounds, does the New Testament shape and prescribe Christian theology? As the contributors explore this question, they address the specific way in which the New Testament does or should shape dogmatics. Part 1 deals with how the Bible informs particular aspects of Christian doctrine and praxis. Part 2 examines how the New Testament has shaped influential theologians of the past century. Part 3 moves from analysis to synthesis, drawing a vision for the New Testament's normative role in forming theology and ethics. - Publisher.
Introduction / Markus Bockmuehl -- Scripture's doctrine. The Septuagint and the "search for the Christian Bible" / J. Ross Wagner -- Is there a New Testament doctrine of the church? / Markus Bockmuehl -- Johannine Christology and Jewish-Christian dialogue / R.W.L. Moberly -- Reading Paul, thinking Scripture / N.T. Wright -- Theology's Bible. The religious authority of Albert Schweitzer's Jesus / James Carleton Paget -- Karl Barth and Friedrich Mildenberger on Scripture in doctrine / Jan Muis -- Rowan Williams on Scripture / John Webster -- The normativity of Scripture and tradition in recent Catholic theology / Benedict Thomas Viviano -- Scripture and theology. Can the truth be learned? : redressing the "theologistic fallacy" in modern biblical scholarship / Alan J. Torrance -- The moral authority of Scripture / Oliver O'Donovan -- The fourfold pattern of Christian moral reasoning according to the New Testament / Bernd Wannenwetsch -- The apostolic discourse and its developments / Kevin J. Vanhoozer.
This book gathers together revised papers originally presented in a series of seminars held at the University of St. Andrews in spring of 2007.
Includes bibliographical references (pages 212-233) and indexes.
Keywords: Bible. -- Theology -- Congresses; Bible. -- Evidences, authority, etc. -- Congresses; Theology, Doctrinal -- Congresses; Conference papers and proceedings